Tawḥīd and Trinity: A Study of Ibn Taymiyyah’s al-Jawāb al Ṣaḥīḥ - Abdullah, Ismail (Intellectual Discourse, 2006)
<!--[if gte mso 9]> Normal 0 false false false EN-MY X-NONE AR-SA <![endif]--><!--[if gte mso 9]> <![endif]--> <!--[if gte mso 10]> <![endif]--> Abstract: Ibn Taymiyyah wrote the six-volumed al-Jawāb al-Ṣaḥīḥ li Man Baddala Dīn al-Masīḥ in response to the short treatise of 24 pages by the Melkite Bishop of Saida in modern Lebanon. A textual analysis of al-Jawāb al- Ṣaḥīḥ proves the versatility of its author and the consistent method he had adopted in correcting the erroneous views held by Christians, Muslim innovators and hypocrites concerning God, Trinity, Incarnation and other aspects. Using revelational and rational arguments, he argues the authenticity of Islam as a way of life and its messenger as a mercy for mankind.